The NiO/CuInS2 Quantum Dots/ZnO Orderly Nanoarrays Transparent Pn Junction Towards Enhanced Photovoltaic Conversion via Dual Functional CuInS2 QDs - Jiaqi Pan; Jingjing Niu; Guangsheng Xiao; Yueyue Fu; Jun Cao; Jingjing Wang; Yingying Zheng; Lei Shi; Chaorong Li (Advanced Materials Interfaces, 2022)
Abstract The transparent pn junction of NiO/CuInS2 quantum dots (QDs)/ZnO orderly nanoarrays has been fabricated via a hybrid approach of sputtering‐hydrothermal‐chemical method. As revealed, the as‐prepared NiO/CuInS2 QDs/ZnO transparent pn junction exhibits decent transparency (≈85%), remarkable photovoltaic enhancement (≈2.5 × 103 folds, PCE of ≈1.19%) than that of intrinsic NiO/ZnO pn junction, and decent stability (4000s’ cycle), which is attributed to that the dual functional CuInS2 QDs with appropriate Fermi level, high QY, and wide bandgap, can optimize photogenerated carrier concentration‐mobility kinetic equilibrium efficiently, while maintaining a better transparency. Furthermore, the ZnO orderly nanoarrays can provide carrier transportation pathway, increase solar efficiency and physical stability.